A Comparison of Top‐Of‐Atmosphere Radiative Fluxes From CERES and ARISE. Issue 24 (21st December 2022) - Taylor, Patrick C.; Itterly, Kyle F.; Corbett, Joe; Bucholtz, Anthony; Sejas, Sergio; Su, Wenying; Doelling, Dave; Kato, Seiji
Abstract: Uncertainty in Arctic top‐of‐atmosphere (TOA) radiative flux observations stems from the low sun angles and the heterogeneous scenes. Advancing our understanding of the Arctic climate system requires improved TOA radiative fluxes. We compare Cloud and Earth's Radiant Energy System (CERES) TOA radiative fluxes with Arctic Radiation‐IceBridge Sea and Ice Experiment (ARISE) airborne measurements using two approaches: grid box averages and instantaneously matched footprints. Both approaches indicate excellent agreement in the longwave and good agreement in the shortwave (SW), within 2σ uncertainty considering all error sources (CERES and airborne radiometer calibration, inversion, and sampling). While the SW differences are within 2σ uncertainty, both approaches show a ∼−10 W m −2 average CERES‐aircraft flux difference. Investigating the source of this negative difference, we find a substantial sensitivity of the flux differences to the sea ice concentration data set. Switching from imager‐based to passive microwave‐based sea ice data in the CERES inversion process reduces the differences in the grid box average fluxes and in the sea ice partly cloudy scene anisotropy in the matched footprints. In the long‐term, more accurate sea ice concentration data are needed to reduce CERES TOA SW flux uncertainties. Switching from imager to passive microwave sea ice data, in the short‐term, could improve CERES TOA SW fluxes in polar regions, additional testing is required. Our analysis indicates that calibration and sampling uncertainty limit the ability to place strong constraints (<±7%) on CERES TOA fluxes with aircraft measurements. Key Points: Overall, excellent agreement is found between the satellite and aircraft top‐of‐atmosphere (TOA) radiative flux observations Substantial sensitivity of the Cloud and Earth's Radiant Energy System (CERES) inversion process is found to the sea ice data set, more accurate sea ice data are needed Calibration and sampling uncertainty limit the ability to place strong constraints (<±7%) on CERES TOA fluxes with aircraft measurements